The relationship between big five personalities and dimensions of transformational leaders in the private sector / Syazwan Saufi and Nurul Haliza Bahari - Saufi, Syazwan; Bahari, Nurul Haliza (2013)
This research attempts to identify which of the Big 5 personalities is believed to have the greatest impact in becoming a charismatic Transformational Leader. It is important that every single employees, in any designation, no matter if they are in managerial level or even executive level, to possess the personalities of a Transformational Leaders. It promises stronger career growth, more effective and efficient performance and also adaptability to change. The result that is produced through this research would facilitate interviewers to detect a persons’ ability to become a transformational leader by observing their personality during an interview session. However, transformational leaders are always initiated by being transactional leaders in the beginning. Thus, transactional leadership aspects have briefly been included to test this theory. The result of the research revealed that conscientiousness and extroversion are the two main personalities that have significant positive relationship transformational leaders. These results were revealed through an investigation that is made by distributing a set of questionnaires that were distributed to 300 respondents from 5 different organizations. The 5 different organizations were Mercedes Benz Malaysia Sdn Bhd, Honda Shared Auto Cars Sdn Bhd, Thursinar Building Maintenance Sdn Bhd, Worldwide Medivest Sdn Bhd, and Aluminium Company of Malaysia Berhad. The questionnaire was constructed in a manner that the subordinates to evaluate their superior (CEO / Managing Director) to test the relationship between their personality and the transformational leadership behaviour. These results will be further discussed in Chapter 4 & Chapter 5.